Analisis Makna Kontekstual Pada Iklan Televisi - Tri Pujiatna; Jaja Jaja; Anggi Krisma Diana (Jurusan Tadris Bahasa Indonesia, 2019)
Human life today is inseparable from the influence of television. Various information can be obtained quickly. To meet the entertainment needs of humans/television viewers, television always inserts advertisements. Besides having commercial purposes, advertising also has the value of the information contained in it. Advertisers, both private and government, try to introduce and invite the public to do what the advertiser wants. Advertisers try to convey messages to consumers or the public in the form of meaningful symbols through mass media which are usually in the form of television, radio, and newspapers. The symbol of meaning is language. Language is used as a communication tool in advertising even though there are many other communication tools, such as images and sounds. The shape of the symbol, namely the language used as a communication tool in advertising has its own meaning.Â Kehidupan manusia saat ini tidak terlepas dari pengaruh televisi. Berbagai informasi dapat diperoleh dengan cepat. Untuk memenuhi kebutuhan hiburan manusia/pemirsa televisi, televisi selalu menyisipkan tayangan iklan. Di samping memiliki tujuan komersil, iklan juga memiliki nilai informasi yang terkandung di dalamnya. Para pengiklan baik swasta maupun pemerintah berusaha untuk memperkenalkan serta mengajak masyarakat dapat melakukan apa yang diharapkan oleh pembuat iklan. Pembuat iklan berusaha untuk menyampaikan pesan kepada konsumen atau masyarakat dalam bentuk lambang bermakna melalui media massa yang biasanya berupa televisi, radio dan surat kabar. Lambang makna yang dimaksud adalah bahasa. Bahasa digunakan sebagai alat komunikasi dalam periklanan walaupun masih banyak lagi alat komunikasi yang lain, seperti gambar, dan bunyi. Bentuk lambang yaitu bahasa yang digunakan sebagai alat komunikasi dalam periklanan memiliki makna tersendiri.